The Traumatic Tube: Bleeding Rectal Ulcer Caused by Flexi-Seal Device - Abhinav Tiwari; Himani Sharma; Khola Qamar; Yaseen Alastal; Thomas Sodeman; Ali Nawras (Case Reports in Gastrointestinal Medicine)
Diarrhea and fecal incontinence are common in critically ill patients and present a challenging problem in patient management. The Flexi-Seal® Fecal Management System is a device to divert the stools away from the patient, thus improving the care to patients with fecal incontinence. There have been only few case reports describing the complications with the use of this device. Here, we present a case of a 77-year-old woman who was admitted due to massive hematochezia while on anticoagulation. She was found to have a large rectal ulcer caused by the Flexi-Seal device, used during the last hospital stay for fecal incontinence. Flexi-Seal device can be effective for the management of incontinence; however, caution should be exercised during handling and pressure from the retention balloon should be relieved periodically.